2017
DOI: 10.11604/pamj.2017.28.248.13171
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic determinants of malnutrition among primary school aged children in Enugu, Nigeria

Abstract: IntroductionSeveral factors including the parental literacy, illness, socioeconomic status, poor sanitation and hygienic practices affect the physical growth of children. The aim of this study was to determine the socio-demographic determinants of malnutrition among primary school aged children in Enugu, Nigeria.MethodsA cross-sectional descriptive study involving primary school children in Enugu was carried out over a 3 month period. Subjects were selected using multistage sampling technique. Weight and heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 13 publications
5
19
3
Order By: Relevance
“…The prevalence of underweight in our study fell within the range reported in other studies done in Southeast Nigeria [14,[34][35][36]. Lower prevalence has however been reported in a neigbouring state among urban dwellers [34,35]. Other studies in Nigeria [5,32,37,38], Ghana [22], Ethiopia [6,7] and India [16] have reported higher prevalence of underweight.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The prevalence of underweight in our study fell within the range reported in other studies done in Southeast Nigeria [14,[34][35][36]. Lower prevalence has however been reported in a neigbouring state among urban dwellers [34,35]. Other studies in Nigeria [5,32,37,38], Ghana [22], Ethiopia [6,7] and India [16] have reported higher prevalence of underweight.…”
Section: Discussionsupporting
confidence: 84%
“…The findings of studies done in other parts of the country among the school-age children varied greatly. The prevalence of underweight in our study fell within the range reported in other studies done in Southeast Nigeria [14,[34][35][36]. Lower prevalence has however been reported in a neigbouring state among urban dwellers [34,35].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Married mothers tend to have better mental states [21][22] because the mother can share the burden and role with her husband. A better parental process will reduce the risk of fives being stunted [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…7 Prevalence of nutritional anaemia is 41.8% and almost half of the school children are malnourished shown in a study conducted in an urban slum area of Delhi by Sunil Gomber. 8 In our study prevalence of anaemia was 73.1%.…”
Section: Discussionmentioning
confidence: 99%